Rancang Bangun Sistem Informasi Monitoring Satuan Pelayanan Pemenuhan Gizi Berbasis Digital Checklist - Fahar Abdul Aziz; Suendri Suendri (Jurnal Teknologi Informasi dan Multimedia, 2026)
This study aims to develop a digital checklist-based operational activity monitoring information system at the Nutrition Fulfillment Service Unit (SPPG). The problem faced is that the monitoring process is still conducted manually using paper-based forms, resulting in unstructured records, difficulty in retrieving historical data, and time-consuming manual reporting. The research method used is Research and Development (R&D), with the system development method using Rapid Application Development (RAD). The research stages include problem identification, data collection through observation, interviews, and literature studies, system design, development, and system implementation. The results of this study are a web-based monitoring information system comprising 43 checklist items across three inspection categories (personal protective equipment, kitchen hygiene, and food ingredient preparation), six main modules, and eight user roles managed through Role-Based Access Control (RBAC). Compared to the previous condition, this system transforms the recording process from manual paper-based to digital, changes data storage from previously difficult-to-retrieve records to automatically documented data, and replaces the manu-al reporting process with automated PDF report generation. Functional testing using the black-box testing method across 8 test scenarios yielded a 100% success rate, confirming that all modules operate in accordance with the designed specifications.